STUDI ANALISA KOORDINASI RELAI GFR INCOMING BUSBAR 20 KV DAN GFR SALURAN UNTUK MENGAMANKAN GANGGUAN SATU PHASA KETANAH DI TRANSFORMATOR 3 GARDU INDUK KAPAL - Krisnayoga Kusuma, I Gede; Dyana Arjana, I Gede; Arta Wijaya, I Wayan (Jurnal Teknologi Elektro, 2017)
Disruption of the distribution system is generally caused by a short circuit that causes overcurrent, one single phase short circuit to ground. Single phase to ground disturbances that occurred at the feeder should be secured by a ground fault relays in feeders. However, due to an error of coordination, interference with the feeder perceived also to the incoming side of the transformer so that ground fault relays on the incoming 20 kV ordered PMT 20 kV at the transformer side open. Working time ground fault relays in feeders Peguyangan is for 0.25 seconds. While working time ground fault relays in the incoming 20 kV is for 0.5 seconds. This indicates that differences in work time relay by 0.25 seconds is considered selective. The event of disruption of the ground phase, GFR relay coordination in securing the area of ??interference must be gradual. Where the value of working time ground fault relays in the base should be longer than the time ground fault relays working on a feeder. It aims to work ground fault relays working order, so that errors can be avoided in the security and do not lead to the spread of disturbed areas.
Keywords: System Protection , OCR and GFR , Ground fault